Public budgetary rules and GDP growth: An empirical study on OECD and twelve european countries. (3rd September 2018) - Beqiraj, Elton; Fedeli, Silvia; Forte, Francesco
Abstract : We study the long‐term effects of budgetary rules on GDP growth rate and analyse the determinants of the short‐term GDP growth dynamics. For both a sample of 19 OECD and a subsample of 12 European countries, we show that, in the long run, improvements in the cyclically adjusted budget balance, as well as increases in the tax burden, have negative effects on GDP growth. The highest effect of fiscal policy on GDP growth would be obtained if the structural deficits were used to increase the market size by reducing the tax burden. In line with Barro (1990), a deficit‐financed reduction of tax burden has a stronger effect for European than for OECD countries, because in Europe the government size with respect to market size is too large. Therefore, if GDP growth is a dominant policy objective, in Europe specific actions should redress the 2012 Treaty toward a reduction of the tax burden.